2011
DOI: 10.4049/jimmunol.1003691
|View full text |Cite
|
Sign up to set email alerts
|

Guanylate Binding Protein 4 Negatively Regulates Virus-Induced Type I IFN and Antiviral Response by Targeting IFN Regulatory Factor 7

Abstract: IRF7 is known as the master regulator in virus-triggered induction of type I IFNs (IFN-I). In this study, we identify GBP4 virus-induced protein interacting with IRF7 as a negative regulator for IFN-I response. Overexpression of GBP4 inhibits virus-triggered activation of IRF7-dependent signaling, but has no effect on NF-κB signaling, whereas the knockdown of GBP4 has opposite effects. Furthermore, the supernatant from Sendai virus-infected cells in which GBP4 have been silenced inhibits the replication of ves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 50 publications
1
59
0
Order By: Relevance
“…Several reports demonstrated that IRF7 is negatively regulated by different mechanisms. Guanylate binding protein 4 (GBP4) disrupts the interactions between TRAF6 and IRF7, leading to reduction of TRAF6-mediated IRF7 ubiquitination [42]. Tripartite motif-containing protein 28 (TRIM28) mediates SUMOylation (post-translational modification mediated by small ubiquitin-like modifier (SUMO) proteins) of IRF7 and inhibits IRF7 transactivation activity [43].…”
Section: Discussionmentioning
confidence: 99%
“…Several reports demonstrated that IRF7 is negatively regulated by different mechanisms. Guanylate binding protein 4 (GBP4) disrupts the interactions between TRAF6 and IRF7, leading to reduction of TRAF6-mediated IRF7 ubiquitination [42]. Tripartite motif-containing protein 28 (TRIM28) mediates SUMOylation (post-translational modification mediated by small ubiquitin-like modifier (SUMO) proteins) of IRF7 and inhibits IRF7 transactivation activity [43].…”
Section: Discussionmentioning
confidence: 99%
“…The IFN bioassay was performed as described previously (20). In brief, supernatants from SeV-infected RAW264.7 cells were overlaid onto L929 cells seeded in a 48-well plate.…”
Section: Ifn Bioassaymentioning
confidence: 99%
“…Polyclonal Ab to Nmi (anti-Nmi) was generated by immunization of rabbits with full-length Nmi expressed by Escherichia coli. Polyclonal Ab to IRF7 (anti-IRF7) was generated as described previously (20). SeV was provided by Wuhan Institutes of Virology, Chinese Academy of Sciences (Shanghai, China).…”
Section: Plasmid Constructs and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations